KONTRIBUSI PEMAHAMAN LINTAS BUDAYA INDONESIA–TIONGKOK DALAM PEMBELAJARAN BIPA BAGI PEMELAJAR TIONGKOK - Kusmiatun, Ari (Widyaparwa, 2024)
In today’s era, the interest in learning the Indonesian language as a foreign language is increasing, especially among learners from China. This increase can be attributed to the economic, cultural, and tourism relations between Indonesia and China, which have driven the demand for Indonesian language proficiency. In this context, it is important for learners to have cross-cultural understanding to avoid cultural conflicts. Drawing on intercultural theory and second language learning, this study aimed to: (1) identify the similarities and differences between Indonesian and Chinese cultures, (2) describe the contributions of both Indonesian and Chinese cultures in BIPA learning for Chinese learners. This study employed a qualitative descriptive approach. Data of this study were words, phrases, or sentences related to Chinese cultural content. Data sources were obtained from five respondents from China who are continuing their studies at Yogyakarta State University. Data collection techniques were conducted through semi-structured interviews. Data analysis used thematic analysis. The results indicate that the cultural differences and similarities between Indonesia and China can contribute to multicultural teaching materials, cross-cultural classroom management, and cross-cultural teaching strategies in BIPA learning.Di era ini, minat untuk mempelajari bahasa Indonesia sebagai bahasa asing semakin meningkat, terutama pemelajar dari Tiongkok. Peningkatan tersebut dapat dikaitkan dengan hubungan ekonomi, budaya, dan pariwisata antara Indonesia dan Tiongkok yang telah mendorong permintaan akan kemampuan berbahasa Indonesia. Dalam konteks ini, penting bagi pemelajar untuk memiliki pemahaman lintas budaya guna menghindari konflik budaya. Dengan menggunakan teori intercultural dan pembelajaran bahasa kedua, penelitian ini bertujuan untuk (1) menemukan persamaan dan perbedaan budaya Indonesia dengan Tiongkok; (2) mendeskripsikan kontribusi kedua budaya Indonesia dengan Tiongkok sebagai Pembelajaran BIPA bagi pemelajar Tiongkok. Penelitian ini termasuk deskriptif kualitatif. Data berupa kata, frasa, atau kalimat terkait muatan budaya Tiongkok. Sumber data diperoleh dari lima responden dari Tiongkok yang sedang melanjutkan studi di Universitas Negeri Yogyakarta. Teknik pengumpulan data dilakukan melalui wawancara semi-terstruktur. Analisis data menggunakan analisis tematik. Hasil menunjukkan bahwa perbedaan dan persamaan budaya Indonesia dan Tiongkok dapat memberikan kontribusi meliputi bahan ajar multikultural, pengelolaan pembelajaran kelas lintas budaya, dan strategi pengajaran lintas budaya dalam pembelajaran BIPA.